Effect of Animation Instructional Strategy on Students’ Achievement in Biology in Senior Secondary Schools in the FCT Abuja, Nigeria - Ekpo, C. G.; Ojelade, I. A.; Simeon, Aruwa (American Journal of Biology and Natural Sciences, 2025)
This study investigated the effect of animation instructional strategy on students’ achievement in biology in senior secondary schools in the FCT Abuja. The study was guided by two research questions and two hypotheses formulated in line with the purpose of the study. The quasi-experimental research design was employed. The population of the study composed of twenty-two thousand, seven hundred and thirty-six (22,736) SS II students from public senior secondary schools in the FCT Abuja, Nigeria. Sample size of the study constituted of one hundred and twenty-five (125) SS II biology students from two intact classes from the sampled schools in the study area. Data collection was conducted using Biology Achievement Test (BAT), Face and content validation of the instrument were carried out by the supervisors of the study and a Biology Education expert from the Department of Science and Environmental Education, Faculty of Education, University of Abuja. The reliability of the instrument was obtained using the Kuder Richardson 21 (KR-21) which yielded an index of 0.87. Descriptive statistics, which involved frequency counts, percentage, mean( ), and standard deviation were used for analyzing data related to the research questions raised while, the independent t-test statistics was used for testing of the formulated hypotheses at 0.05 level of significance. Results showed that the animation instructional strategy had significant effect on students’ achievement, without gender differences. It was recommended that teachers should be provided with training and resources to effectively use animation instructional strategy to teach Biology since it enhances students’ achievement. Every student should be given equal opportunity irrespective of gender during the use of animation instructional strategy to enhance their academic achievement since it has been found to be gender friendly.